Assessing the potential of acoustic indices for protected area monitoring in the Serra do Cipó National Park, Brazil. (January 2021) - Campos, Ivan Braga; Fewster, Rachel; Truskinger, Anthony; Towsey, Michael; Roe, Paul; Vasques Filho, Demival; Lee, William; Gaskett, Anne
Highlights: Acoustic Regions enable identifying sounds that drive soundscape differences. Each Acoustic Region is defined by a specific frequency range and time period. Using acoustic indices as filters enables detecting the Acoustic Region of interest. The Acoustic Region of interest is the one that differs most between sites. Acoustic Region of interest is likely to be optimal for protected areas monitoring. Abstract: Protected areas (PAs) monitoring is a technical bottleneck that limits the implementation of decision-making processes for natural resource and wildlife management. Recent methodological advances make passive acoustic monitoring and associated acoustic index analysis an increasingly suitable method for PAs monitoring. Acoustic indices are mathematical filters that can provide standardised comparative information about the acoustic energy, which can be applied to compare communities. In this study we test whether acoustic indices are sufficiently sensitive to detect differences in the soundscape within each of the four seasons between a PA (the Serra do Cipó National Park, Brazil) and a surrounding farmland area. Statistical analysis of results from 12 acoustic indices is used to identify which of 20 acoustic regions, defined by frequency range and time period, present the greatest differences between the two sites. The soundscapes of the two sites differed most in autumn within the acoustic region 6, representing 05:30 – 09:00am and a range of 0.988–3.609 kHz. This acoustic region exhibited significant differences for all the 12 indices tested. Visual examination of 65 long-duration false-colour (LDFC) spectrograms resulted in the selection of 865 (from 1365) sound files with acoustic events within the range of acoustic region 6. Sonotype analysis of the 865 files showed that the soundscape outside the park is strongly influenced by human activity, with domestic animals rare in the park soundscape (1% of the sound files), but very common in the surrounding farmland environment (63% of the sound files). The main goal of monitoring programmes detecting biodiversity trends across space and time, which is here achieved via passive acoustic monitoring and acoustic indices. This confirms the utility of the techniques used here for PA monitoring, especially for detecting trends in anthropogenic disturbance, which is a common threat to natural habitats in parks and reserves in the tropics.